Perception of hypotheticality in technology-based business ideas: effects on Opportunity Beliefs from a Construal Level Theory perspective - Andrade-Valbuena, Nelson A.; Sergio Olavarrieta, S.; Juan Pablo Torres, C. (Frontiers in Psychology, 2024)
This research investigates how entrepreneurs perceive the hypothetical nature of technologies (based on situations that are often imagined or theoretical) as a foundation for entrepreneurial endeavors and how this perception influences the formation of business Opportunity Beliefs. Drawing on the Construal Level Theory, we explore the relationship between the perceived hypotheticality of technologies and Opportunity Beliefs. Two experimental studies are conducted to examine these relationships, with Study 1 (n = 177 entrepreneurs) focusing on the perception of innovative technologies as more distant or hypothetical, and Study 2 (n = 404 entrepreneurs) delving into how the perceived distance to technology influences Opportunity Beliefs. The results indicate that entrepreneurs view more innovative technologies as more hypothetical and that hypotheticality mediates the relationship between the perceived degree of innovation and Opportunity Beliefs. We find evidence that Entrepreneurs tend to view the feasibility and fit/alignment of business opportunities more favorably when they perceive the psychological distance (hypotheticality) of the opportunity as closer rather than more distant. However, the difference this difference is nonsignificant in how they evaluate the desirability of the opportunity in any psychological distance. These results provide insight into the cognitive processes of entrepreneurs and offer implications for understanding how entrepreneurs perceive and evaluate business opportunities.